2003
DOI: 10.1002/j.1939-4640.2003.tb02666.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation and Age‐Related Changes in Human Semen Parameters

Abstract: Although semen quality has been discussed extensively with regard to age and season in the andrology literature, the results vary and firm conclusions are still outstanding. To investigate seasonal and age-related variations in human semen parameters, we analyzed data that were collected from an andrology clinic population. We performed a retrospective review of 551 semen analysis records collected from 1989 to 2000 from the Vincent Memorial Andrology Laboratory at Massachusetts General Hospital. Semen volume,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(81 citation statements)
references
References 20 publications
3
75
3
Order By: Relevance
“…However, in an earlier study they found inverse associations between age and sperm concentration, motility and morphology. They attributed those findings to an older population of males compared to their earlier study (63). Also, age was significantly positively correlated with the studied apoptotic markers.…”
Section: Discussionmentioning
confidence: 57%
“…However, in an earlier study they found inverse associations between age and sperm concentration, motility and morphology. They attributed those findings to an older population of males compared to their earlier study (63). Also, age was significantly positively correlated with the studied apoptotic markers.…”
Section: Discussionmentioning
confidence: 57%
“…On the reproductive health side, prior work suggests that exposure to extreme heat negatively affects semen quality and testosterone levels (Levine, 1991;Dada et al, 2001;Chen et al, 2003;Svartberg et al, 2003), and interferes with menstruation, ovulation, and implantation (Meade and Earickson, 2000;Ellison et al, 2005).…”
Section: IImentioning
confidence: 99%
“…Further, the semen quality of Japanese fertile men is similar to Danish men, which has lowest values among the European males [24]. Meanwhile, a number of studies indicate the association of increased age with decline in the semen characteristics [31][32][33][34] whereas, a few reports showed no such association [35][36]. Altogether, there is a possibility that combination of genetic and environmental factors including nutritional, geographical, life style, and their interactions accounts for variations observed in the semen parameters that are studied across different populations.…”
Section: Introductionmentioning
confidence: 95%